Characterization of the Primary Human Trophoblast Cell Secretome Using Stable Isotope Labeling With Amino Acids in Cell Culture - Rosario, Fredrick J.; Pardo, Sammy; Michelsen, Trond M.; Erickson, Kathryn; Moore, Lorna; Powell, Theresa L.; Weintraub, Susan T.; Jansson, Thomas (Frontiers in Cell and Developmental Biology, 2021)
The placental villus syncytiotrophoblast, the nutrient-transporting and hormone-producing epithelium of the human placenta, is a critical regulator of fetal development and maternal physiology. However, the identities of the proteins synthesized and secreted by primary human trophoblast (PHT) cells remain unknown. Stable Isotope Labeling with Amino Acids in Cell Culture followed by mass spectrometry analysis of the conditioned media was used to identify secreted proteins and obtain information about their relative rates of synthesis in syncytialized multinucleated PHT cells isolated from normal term placental villus tissue (n=4/independent placenta). A total of 1344 proteins were identified, most of which have not previously been reported to be secreted by the human placenta or trophoblast. The majority of secreted proteins are involved in energy and carbon metabolism, glycolysis, biosynthesis of amino acids, purine metabolism and fatty acid degradation. Histone family proteins and mitochondrial proteins were among proteins with the slowest synthesis rate whereas proteins associated with signaling and the plasma membrane were synthesized rapidly. There was a significant overlap between the PHT secretome and proteins known be secreted to the fetal circulation by the human placenta in vivo. The generated data will guide future experiments to determine the function of individual secreted proteins and will help us better understand how the placenta controls maternal and fetal physiology.